Developing gene therapy for inherited retinal degenerations - Yusuf, IH (2022)
The aim of this thesis was to evaluate the efficacy and safety of retinal gene therapy in a pre-clinical model of CDHR1-associated retinal degeneration – a hitherto untreatable, blinding disorder.